Chinese Students’ Resilience in Making Post-Graduation Plans Under the US-China Geopolitical Tensions - Li, Xiaojie (Journal of International Students, 2022)
As the US-China geopolitical tensions escalated, this study sought to investigate how Chinese students respond to the political circumstances when making their post-graduation plans. Drawing from interviews among 15 Chinese international students who graduated from a US university, this study found that most Chinese students did not change their post-graduation plans due to the heightened tensions between the US and China, while they enacted agency to overcome the difficulties imposed by the geopolitical context. This study challenged the deficit view of international student research by indicating that Chinese students could adapt to a set of perspectives, transform these perspectives into actions, and leverage useful resources to protect their career and life aspirations. The study also warned the danger of the continuity of the anti-China political rhetoric and emphasized the role of higher education institutions in buffering the negative political impact and supporting Chinese and all international students.